2022
DOI: 10.1038/s41377-022-00875-9
|View full text |Cite
|
Sign up to set email alerts
|

Up and down the spectrum: upconversion nanocrystal and semiconductor material fused into a single nanocomposite

Abstract: A nanocomposite consisting of a cubic EuSe semiconductor material grown on a hexagonal upconversion nanoparticle has overcome the crystal lattice mismatch that typically prevents the epitaxial growth of such heterogeneous nanocrystals. Eu3+ at the interface layer shows its characteristic red emission band both under UV excitation light due to energy transfer from the semiconductor and under NIR excitation light due to energy transfer after photon-upconversion. Data storage and security applications are suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies also reported lanthanides due to their comparable ionic radii can be substituted for one another in crystalline host matrices; they can also be added in various combinations and introduced in varying concentrations without significantly altering the crystal structure [26]. Since the ionic diameters of Pr 3+ (1.82 Å) and Y 3+ (1.80 Å) are similar, and the valence of Pr 3+ and Y 3+ are the same, Pr 3+ can substitute for the Y 3+ sites [27].…”
Section: Structural Analysismentioning
confidence: 99%
“…Studies also reported lanthanides due to their comparable ionic radii can be substituted for one another in crystalline host matrices; they can also be added in various combinations and introduced in varying concentrations without significantly altering the crystal structure [26]. Since the ionic diameters of Pr 3+ (1.82 Å) and Y 3+ (1.80 Å) are similar, and the valence of Pr 3+ and Y 3+ are the same, Pr 3+ can substitute for the Y 3+ sites [27].…”
Section: Structural Analysismentioning
confidence: 99%